2012
DOI: 10.1128/aem.01325-12
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affect Acidobacterial Communities below the Subgroup Level in Grassland and Forest Soils

Abstract: In soil, Acidobacteria constitute on average 20% of all bacteria, are highly diverse, and are physiologically active in situ. However, their individual functions and interactions with higher taxa in soil are still unknown. Here, potential effects of land use, soil properties, plant diversity, and soil nanofauna on acidobacterial community composition were studied by cultivation-independent methods in grassland and forest soils from three different regions in Germany. The analysis of 16S rRNA gene clone librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
162
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 299 publications
(198 citation statements)
references
References 60 publications
28
162
5
3
Order By: Relevance
“…Bacteria from the genus Burkholderia are typical soil inhabitants, and certain Burkholderia strains are resistant to hydrocarbons and are used in the bioremediation of oil-polluted sites (Bacosa et al, 2012;Weisskopf et al, 2011;Hamamura et al, 2008;Adetutu et al, 2013). Band 3 (KF926426-KF926429), which is sensitive to oily and radioactive components in the waste samples (not seen in contaminated H -and R-samples), was genetically similar to Hydrogenobacter hydrogenophilus (Z30242) uncultured Acidobacteria isolated from unpolluted grassland and forest soils (HQ598830, HQ599021; Naether et al, 2012) and an uncultured Chlorobiales bacterium found in a uranium mining waste pile (AJ295649, AJ536877; Selenska-Pobell, 2002). Band 4 (KF926430-KF926433), which dominated in H -columns, was related to an uncultured bacterium from mineral soils of the Atacama desert (JX098489, JX098426; Lynch et al, 2012) and actinomycetes from the genus Catenulispora (CP001700, AJ865857; Busti et al, 2006) as well as strains isolated from gasoline-polluted sites (or able to degrade hydrocarbons; JQ919514; Hilyard et al, 2008), including a Parvibaculum strain that catabolizes linear alkylbenzene sulfonate (AY387398; Schleheck et al, 2004).…”
Section: Bacterial Species Identified After Sequencing Of Bands Obtaimentioning
confidence: 99%
“…Bacteria from the genus Burkholderia are typical soil inhabitants, and certain Burkholderia strains are resistant to hydrocarbons and are used in the bioremediation of oil-polluted sites (Bacosa et al, 2012;Weisskopf et al, 2011;Hamamura et al, 2008;Adetutu et al, 2013). Band 3 (KF926426-KF926429), which is sensitive to oily and radioactive components in the waste samples (not seen in contaminated H -and R-samples), was genetically similar to Hydrogenobacter hydrogenophilus (Z30242) uncultured Acidobacteria isolated from unpolluted grassland and forest soils (HQ598830, HQ599021; Naether et al, 2012) and an uncultured Chlorobiales bacterium found in a uranium mining waste pile (AJ295649, AJ536877; Selenska-Pobell, 2002). Band 4 (KF926430-KF926433), which dominated in H -columns, was related to an uncultured bacterium from mineral soils of the Atacama desert (JX098489, JX098426; Lynch et al, 2012) and actinomycetes from the genus Catenulispora (CP001700, AJ865857; Busti et al, 2006) as well as strains isolated from gasoline-polluted sites (or able to degrade hydrocarbons; JQ919514; Hilyard et al, 2008), including a Parvibaculum strain that catabolizes linear alkylbenzene sulfonate (AY387398; Schleheck et al, 2004).…”
Section: Bacterial Species Identified After Sequencing Of Bands Obtaimentioning
confidence: 99%
“…In particular, no isolate of sd6 is available, although the latter represents the dominant subdivision in many soils (Barns et al, 1999;Foesel et al, 2014;Jones et al, 2009). 16S rRNA sequence analyses revealed that members of sd6 dominate in soils with a neutral or (slightly) basic pH, together with bacteria of sd4, whereas members of sd 1 and 3 prevail in soils which are (slightly) acidic Jones et al, 2009;Naether et al, 2012). About half of the soils on earth have a neutral or (slightly) basic pH (www.fao.org/soils-portal/soil-survey/soil-properties/chemical-properties/en/).…”
mentioning
confidence: 99%
“…According to molecular studies, members of the Acidobacteria are among the most abundant bacteria in soil (35) and may represent up to 20% of the total bacteria in soil communities (36). Recent genome sequencing projects targeting bacteria belonging to this group promoted insights into their lifestyle and revealed them to be best suited to low-nutrient conditions (37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%